The Building Religious Character of Children Orphanage at Nurul Jannah Kudus - Rochanah Rochanah; Fina Izatul Muna; Bambang Ariyanto (CV. Creative Tugu Pena, 2022)
The problem raise in this study was how efforts to shape religious character and how the description of the sacred character that was embedded in children orphanage at Nurul Jannah Kudus. The research aims to analyze the various efforts made by Nurul Jannah Kudus in shaping the religious character of children orphanage and sacred character that was embedded in children orphanage at Nurul Jannah Kudus. The method used descriptive-analytical. The data collection techniques used observation, interviews, and documentation. The results showed that to shape religious character in children, namely conducting routine religious activities, strict supervision and embedding awareness in children, applying discipline to children, applying the habituation method in carrying out routine activities. In applying the advice method was by caregivers and ustadz or ustadzah. Furthermore, the description of the religious character was not neglect the obligations of a human being to worship Allah SWT, independence, always instilling honesty in every matter, discipline in carrying out rules and activities, a sense of concern for others, responsibility in doing anything, creativity in doing specific fields. Keywords: Building Religious Character, Building Children Character, Religious Character